Advances in Polymer Composite Research : Integrating Experimental and Computational Approaches - Kumar Maurya, Atul; Manik, Gaurav; Kumar Sethi, Sushanta (CRC Press, Taylor & Francis Group, 2025)
This book emphasizes the importance of experimental characterization techniques and computational modeling tools in polymer composites. The topics covered include finite element analysis, computational fluid dynamics, molecular dynamics simulations, machine learning, material informatics, multiscale modeling, advanced characterization techniques, and the emerging field of nanocomposites. Each chapter provides detailed discussions, case studies, and examples to illustrate the practical application of these techniques in polymer composite research.Features: Offers a comprehensive exploration of polymer composites encompassing both experimental and computational approaches. Showcases most recent findings, methodologies, technologies, and applications in the field. Explores real-world case studies, industrial applications, and potential commercialization opportunities. Discusses the understanding, analysis, and design of polymer composites. Includes LAMMPS-, Ansys-, ABAQUS-, and Materials Studio-based simulation examples. This book is aimed at graduate students and researchers in polymers, polymer composites, and materials science.
Keywords: Composite materials.; Polymers.; elektronické knihy; electronic books